Problems of variation in translation: a case study of the lexical unit: ‘ FACILITIES’ - M Y Kupriyanova (Russian journal of linguistics: Vestnik RUDN, 2014)
The article looks into the number of translation variants of the polysemic lexical unit ‘ facilities’ in the academic environment. It justifies the narrowing down of synonymic terms in translation into Russian. Variants of translating the word ‘ facilities’ in different contexts are suggested.